Pediatric Dental Emergency Pattern and Dental Care Provided during COVID-19 Pandemic Lockdown at a Tertiary Care Center in Kathmandu, Nepal - Limbu, Senchhema; Dikshit, Parajeeta; Malla, Manisha; Verma, Lokesh; Khapung, Anju (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Introduction: Pediatric dental management is difficult in its own way which was even more challenging during COVID-19 outbreak and lockdown period. Constrained dental providing clinics and hospitals severely compromised the pediatric dental needs and services.Objective: The aim of this study was to describe pattern of dental emergencies encountered and services provided to the pediatric patients visiting a dental hospital during the first lockdown period in Kathmandu, Nepal.Methods: A cross sectional study was done from 24 March 2020 to 21 July 2020 among the pediatric patients who visited dental hospital during lockdown. Data was collected from questionnaire and dental case history sheet, and statistically analyzed in Statistical Package of Social Sciences (SPSS) version 20.Results: Of the total 172 pediatric patients of mean age 8.3± 2.60 years, majority were males (59.3%) and of 6-12 age group (76.2%). Major complain was mobile/retained teeth (38.4%) and most common diagnosis was exfoliating mobility (23.3%). According to American Dental Association (ADA, 2020) guidelines, urgent dental care (46.5%) followed by non-emergency dental care (43.6%) were mostly found. The predominant procedures were emergency (68.6%) and least was elective (9.3%) and treatment given to majority was extraction (51.8%).There was a statistically significant association between age group and pediatric dental care (ADA).Conclusions: The findings of this study regarding dental emergency encountered and definitive treatment received even during pandemic lockdown can be helpful in finding out how dental care was provided and can be applicable in similar future pandemics.